Randomized Trial of Dilute Povidone-Iodine Soak and Scrub for Orthopaedic Foot and Ankle Surgery. (December 2021) - Mehraban, Nasima; Wakefield, Connor; Rossi, David; Lin, Johnny; Lee, Simon; Hamid, Kamran S.; Bohl, Daniel D.
Background: There is no consensus as to which skin antiseptic solution is most effective at reducing infection following orthopaedic foot and ankle surgery. The purpose of this study is to determine if the addition of a dilute povidone-iodine soak and scrub to a standard preparation with alcohol and chlorhexidine decreases positive bacterial culture rates from the hallux nailfold. Methods: In this prospective, randomized controlled trial, 242 subjects undergoing orthopaedic foot and ankle surgery were randomized to one of 2 groups. The control group received our standard 2-step skin antiseptic preparation of an alcohol scrub (step 1) followed by chlorhexidine/alcohol paint (step 2). The intervention group received a 3-minute dilute povidone-iodine soak and scrub followed by that same standard 2-step skin preparation. Immediately before skin incision, culture swabs were taken from the hallux nailfold of both groups. Results: Of the 257 subjects enrolled and randomized, 242 (94.2%) completed the study, satisfying the a priori sample size requirement of 242 subjects. There were no crossovers between groups. There were no differences in baseline characteristics between groups ( P > .05 for each). There was no difference in bacterial growth rates between groups (26.8% growth in the intervention group vs 26.9% growth in the control group, P = .991). Conclusion: The hallux nailfold is one of the most difficult to sterilize areas prior to orthopaedic foot and ankle surgery. This randomized controlled trail found no benefit to adding a 3-minute dilute povidone-iodine soak and scrub to a standard skin preparation with alcohol and chlorohexidine. Level of Evidence: Level I, randomized controlled trial.